Layanan Konseling Individu Dan Kelompok Pada Wali Murid SD IT Al Uswah Singosari Malang - Mustika, Ulfa Dyah; Indah H, Sri Wiworo Retno; Refangga, Galih Setyo (Civiliza Publishing, 2025)
Individual and group counseling services for parents in primary schools are an important initiative in supporting children’s development. Parents play a crucial role in guiding and facilitating their children’s development in various aspects of life, including educational, social, and emotional. However, it is not uncommon for parents to face challenges in understanding and responding appropriately to their children’s psychological needs. Individual and group counseling are effective approaches in providing psychological support to children, especially in addressing issues such as academic stress, social problems, and interpersonal skills development. Through these counseling services, children can be helped to recognize and overcome the challenges they face, and improve their overall well-being. In this context, the integration of legal knowledge becomes relevant because it provides the necessary framework in addressing the various issues that may arise, including legal protection of children’s and parents’ rights, legal procedures related to specific cases, and protection of privacy in the context of counseling. The application of legal knowledge in counseling services not only safeguards individual rights but also ensures that the approach taken is in accordance with applicable ethical and legal norms. Individual and group counseling services for parents in primary schools are an important initiative in supporting children’s development.